Resources for Educating, Training, and Mentoring All Physicians Providing Palliative Care - Downar, James (J Palliat Med, 2017)
This article presents a rapid review of the published literature and available resources for educating Canadian physicians to provide palliative and end-of-life care. Several key messages emerge from the review. First, there are many palliative care educational resources already available for Canadian physicians. Second, the many palliative care education resources are often not used in physician training. Third, we know that some palliative care educational interventions are inexpensive and scalable, while others are costly and time-consuming; we know very little about which palliative care educational interventions impact physician behavior and patient care. Fourth, two palliative care competency areas in particular can be readily taught: symptom management and communication skill (e.g., breaking bad news and advance care planning). Fifth, palliative care educational interventions are undermined by the “hidden curriculum” in medical education; interventions must be accompanied by continuing education and faculty development to create lasting change in physician behavior. Sixth, undergraduate and postgraduate medical training is shifting from a time-based training paradigm to competency-based training and evaluation. Seventh, virtually every physician in Canada should be able to provide basic palliative care; physicians in specialized areas of practice should receive palliative care education that is tailored to their area, rather than generic educational interventions. For each key message, one or more implications are provided, which can serve as recommendations for a framework to improve palliative care as a whole in Canada.